Ontological (In-) Security and the Dark Night of the Soul: Political Prisoners’ Sense-Breaking - Kung, Lap Yan (Asia journal of theology, 2023)
This study reflects on how Christian political prisoners in Hong Kong utilize their Christian resources to articulate and live with the ontological insecurity caused by incarceration. Hong Kongers consider political prisoners to be sufferers for Hong Kong rather than criminals, an interpretation that corresponds to the Christian notion of redemptive suffering. The Christian political prisoners interviewed in this study see their days in prison as the dark night of the soul in which a generative sense-making has emerged. The days in the dark night are painful, but ironically, their spirituality in the dark night exposes the injustice of rule by law, disempowers the threat of demoralization, changes the game theory from prisoner’s dilemma to warden’s dilemma, and illustrates that imprisonment can be turned to an unexpected platform for personal growth. This sense-breaking, despite as yet being weak, gives birth to a social narrative characterized by suffering in solidarity in contrast to the official narrative,"from chaos to order, from order to prosperity."